Kemampuan Nyurat Aksara Bali menggunakan Aplikasi Papan Ketik (Patik) Bali pada Android - Rai, Ida Bagus (LOKABASA, 2019)
This study aims to (1) explain the procedure for using TPS type cooperative learning models with the PaTik Bali application in the Balinese script writing course for Undiksha Singaraja Balinese language education students, (2) the ability of students in the Balinese Undiksha Singaraja language learning program, after using the learning model TPS cooperative type with the application of PaTik Bali in writing Balinese script, and (3) the opinion of students of the Undiksha Singaraja Bali language education program, about the TPS type cooperative learning model in writing Balinese script. This research uses descriptive qualitative and quantitative data. The subject in this research was the lecturer writing the Balinese Undiksha Singaraja Balinese language education program, and the object in this study was learning using the type of cooperative learning model TPS. Data collection methods used were observation, tests and questionnaires. The results of the study include (1) the procedures for lecturers using the TPS type cooperative learning model with the PaTik Bali application in the Balinese script according to the learning plan that has been made, (2) using the TPS type cooperative learning model with the PaTik Bali Application can improve the ability of students in the Study Program Undiksha Singaraj's Balinese language education, and (3) the opinion of Undiksha Singaraja's Balinese language education program students, in using TPS type cooperative learning models with the PaTik application provide good responses to improve students' ability to write Balinese script. There is a positive and significant influence in using the type of TPS cooperative learning model with the application of PaTik Bali in improving the ability to write Balinese script students of the Balinese Undiksha Singaraja language education program.AbstrakPenelitian ini bertujuan untuk (1) menjelaskan tata cara menggunakan model pembelajaran kooperatif tipe TPS dengan aplikasi PaTik Bali dalam mata kuliah menulis aksara Bali mahasiswa Prodi pendidikan bahasa Bali Undiksha Singaraja, (2) kemampuan mahasiswa Prodi pendidikan bahasa Bali Undiksha Singaraja, setelah menggunakan model pembelajaran kooperatif tipe TPS dengan aplikasi PaTik Bali dalam menulis aksara Bali, dan (3) pendapat mahasiswa Prodi pendidikan bahasa Bali Undiksha Singaraja, tentang model pembelajaran kooperatif tipe TPS dalam menulis aksara Bali. Penelitian ini menggunakan data deskriptif kualitatif dan kuantitatif. Subjek dalam penelitan ini adalah dosen menulis aksara Bali Prodi pendidikan bahasa Bali Undiksha Singaraja, dan objek dalam penelitian ini adalah pembelajaran menggunakan model pembelajaran kooperatif tipe TPS. Metode pengumpulan data yang digunakan adalah observasi, tes dan angket/kuesioner.  Hasil  penelitian  meliputi  (1)  tata  cara dosen  menggunakan model pembelajaran kooperatif tipe TPS dengan aplikasi PaTik Bali dalam mata kuliah nyurat aksara Bali sesuai rencana pembelajaran yang telah dibuat, (2)  menggunakan  model  pembelajaran  kooperatif  tipe  TPS  dengan  Aplikasi PaTik Bali bisa meningkatkan kemampuan mahasiswa Prodi pendidikan bahasa Bali Undiksha Singaraj, dan (3) pendapat mahasiswa Prodi pendidikan bahasa Bali Undiksha Singaraja, dalam menggunakan model pembelajaran kooperatif tipe TPS dengan aplikasi PaTik memberikan respon yang baik untuk meningkatkan kemampuan mahasiswa menulis aksara Bali. Ada pengaruh yang positif dan signifikan dalam menggunakan model pembelajaran kooperatif tipe TPS dengan aplikasi PaTik Bali dalam meningkatkan kemampuan menulis aksara Bali mahasiswa Prodi pendidikan bahasa Bali Undiksha Singaraja.